2013
DOI: 10.1021/es304329w
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Ag- and TiO2-(Nano)particles from Textiles into Artificial Sweat under Physical Stress: Experiments and Exposure Modeling

Abstract: Engineered nanoparticles (ENP) are increasingly used to functionalize textiles taking advantage, e.g., of the antimicrobial activity of silver (Ag)-ENP or the UV-absorption of titania (TiO2)-ENP. Mobilization and migration of ENPs from the textile into human sweat can result in dermal exposure to these nanoobjects and their aggregates and agglomerates (NOAA). In this study we assessed exposure to NOAA migrating from commercially available textiles to artificial sweat by an experimental setup that simulates wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 27 publications
(59 reference statements)
3
95
2
1
Order By: Relevance
“…Recent studies have shown that Ag NP-containing textiles can release significant quantities of Ag in water (Benn and Westerhoff, 2008;Benn et al, 2010;Pasricha et al, 2012), washing liquid (Geranio et al, 2009;Lorenz et al, 2012;Impellitteri et al, 2009), and artificial sweat (Kulthong et al, 2010;Geranio et al, 2009;von Goetz et al, 2013a).…”
Section: Ac5: Fabrics Textiles and Apparelmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that Ag NP-containing textiles can release significant quantities of Ag in water (Benn and Westerhoff, 2008;Benn et al, 2010;Pasricha et al, 2012), washing liquid (Geranio et al, 2009;Lorenz et al, 2012;Impellitteri et al, 2009), and artificial sweat (Kulthong et al, 2010;Geranio et al, 2009;von Goetz et al, 2013a).…”
Section: Ac5: Fabrics Textiles and Apparelmentioning
confidence: 99%
“…A number of studies have attempted to mimic one of the possible real-life scenarios of nano-Ag textile use by immersing the fabrics into artificial sweat at body temperature (Kulthong et al, 2010;von Goetz et al, 2013a;Yan et al, 2012;Stefaniak et al, 2014). The quantities of Ag released varied substantially for different fabrics and pH values, and was most likely dependent on the amounts of silver in fabrics, the fabric quality and the composition and pH of artificial sweat applied.…”
Section: Ac5: Fabrics Textiles and Apparelmentioning
confidence: 99%
“…In addition, if uncontrolled evaporation of the solvent occurs during the drying process, it can cause inhomogeneous distribution of NPs on the fibers due to migration phenomena. 16 This drying procedure also limits the roll-to-roll speed of the textile finishing line. Another drawback of the wet-finishing process is that the reproducibility and controllability of nanomaterial deposition are frequently inhibited by the batch-type operation.…”
Section: Introductionmentioning
confidence: 99%
“…In the US, in contrast, the use of nanosilver in food containers is possible (EPA 2010, von Goetz et al 2013), but has to be registered.…”
Section: Paints/ Coatings / Pigmentsmentioning
confidence: 99%